Cyclic filtration behavior of structured cattail fiber assembly for oils removal from wastewater. Issue 14 (18th July 2018) - Cao, Shengbin; Dong, Ting; Xu, Guangbiao; Wang, Fumei
ABSTRACT: Structured cattail fiber assembly was reported as the filter for removing oils from runoff. The oil-wetted filter was recovered by rotational centrifugation and reused in the next filtration. The cyclic filtration behavior of the assembly was characterized by oil removal efficiency, oil sorption capacity, influence of packing density and number of filtration cycles. The efficiency of liquid removal and oil recovery from the centrifuged filter were also investigated. Cattail filters showed an excellent oil cyclic filtration performance which was found to have a close relationship with the inner structural characteristic of the fibers. The filters removed vegetable oil and diesel completely from runoff in the initial 40–90 min and 30–60 min in the first cycle, respectively, after which the oils broke through the filter's body and 29.4–71.4 L and 21.0–46.2 L of clean water were collected. The time of breakthrough was decreased with decreasing cattail's packing density. The wetted filters which absorbed up to 693.11 g (14.81 g/g) of vegetable oil and 497.02 g (10.62 g/g) of diesel took separately 7 min and 30 s to be recovered. Seventy-five to ninety percent of liquids were removed and 70–93% of oils were re-collected.